2014
DOI: 10.1088/0953-8984/26/31/315001
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of FeO(1 1 1)/Ag(0 0 1): undulation of hexagonal oxide monolayers due to square lattice metal substrates

Abstract: Iron oxide monolayers are grown on Ag(0 0 1) via reactive molecular beam epitaxy (metal deposition in oxygen atmosphere). The monolayer shows FeO stoichiometry as concluded from x-ray photoemission spectra. Both low energy electron diffraction as well as scanning tunneling microscopy demonstrate that the FeO layer has a quasi-hexagonal (1 1 1) structure although deposited on a surface with square symmetry. Compared to bulk values, the FeO(1 1 1) monolayer is unidirectionally expanded by 3.4% in [Formula: see t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…The FeO stoichiometry is commonly observed for one layer thick films grown on various substrates with both hexagonal [10][11][12][13][14] and square [15][16][17][18][19] symmetry. Intriguingly, in most cases such films grow with an in-plane structure similar to (111) termination of bulk wüstite, where the surface is unstable due to the polar nature of the (111) termination of this rock-salt-like compound [20].…”
Section: Introductionmentioning
confidence: 99%
“…The FeO stoichiometry is commonly observed for one layer thick films grown on various substrates with both hexagonal [10][11][12][13][14] and square [15][16][17][18][19] symmetry. Intriguingly, in most cases such films grow with an in-plane structure similar to (111) termination of bulk wüstite, where the surface is unstable due to the polar nature of the (111) termination of this rock-salt-like compound [20].…”
Section: Introductionmentioning
confidence: 99%
“…(100)-Oriented FeO and Fe 3 O 4 films of nanometerscale thickness have been reported by Arbreu et al, 27 Lopes et al, 28 and Bruns et al 29 by either deposition of iron in a background of O 2 or by postoxidation of a deposited iron film. A second study by Bruns et al 30 also reported the growth of an FeO(111)-like phase at submonolayer coverages which was proposed to have a monolayer structure like that of FeO on Pt. Waddill et al, 31 and Schlueter et al 32 also identified (111)-oriented FeO growing at low coverage on Ag(111) by low energy electron diffraction and X-ray diffraction, respectively.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Although growth of FeO(111) monolayers on metal surfaces other than platinum has been reported, these studies have been largely limited to structural characterization and redox properties, and little information about the effect of the substrate on adsorption properties is available. However, there is evidence from published studies that the substrate can influence these properties.…”
Section: Figurementioning
confidence: 99%